Pancreatic malignancy presenting as duodenal ulcer (D1). (November 2017) - Al-Amin, Azzam; Stephenson, Tim; Shiwani, Muhammad
Abstract : Introduction: Malignant ulcer at the duodenal bulb is extremely rare. The commonest cause of ulcers here is peptic ulcer disease. Therefore the routine biopsy of ulcer at D1 is not routinely recommended, to avoid complications. Case description: An 83-year-old lady presented to the surgical outpatient clinic with upper abdominal pain radiating to left side of her chest. She had recent history of significant weight loss, approximately 22kg. Abdominal examination was unremarkable. Results and Conclusions: Haemoglobin and Liver Function Tests were normal. Gastroscopy showed one large 3cm ulcer with a shaggy base and rolled over margin in the first part of the duodenum (D1) which appeared malignant. Initial histology confirmed adenocarcinoma of uncertain origin. CT scan showed a 2.9x3.7cm partially cystic mass lesion in the head of the pancreas that was locally invading into the first part of the duodenum, with no evidence of metastases. Immunohistochemistry showed strong Ca19.9 positive, favouring primary pancreatic origin. Take home message: Pancreatic cancer presenting as an ulcer in D1 is very rare. If a suspicious looking ulcer is found endoscopically at D1, it should be biopsied. A CT scan of the abdomen is also important in the work-up of such cases.